2020
DOI: 10.1016/j.jaim.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate-derived anthocyanin regulates MORs-cAMP/CREB-BDNF pathways in opioid-dependent models and improves cognitive impairments

Abstract: Background Pomegranate ( Punica granatum ) is one of the oldest known edible fruit. Recently, there has been an increased interest in this fruit as a functional food for health benefits due to its use in disease prevention and promotion of overall health wellness. Objective This study aims to investigate the effects of pomegranate extract for the development of non-opioid substitution therapy for in-vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…elderly people) to produce sufficient or required health benefits. 52 Recently, it has been reported that administration of ET-rich pomegranate extract and EA improved cognitive impairments and brain dysfunction by up-regulating CREB/BDNF signaling in rodents, 53,54 which is in line with our results. It seems that CREB signaling may be a common target of both UroA and its precursors.…”
Section: Discussionsupporting
confidence: 91%
“…elderly people) to produce sufficient or required health benefits. 52 Recently, it has been reported that administration of ET-rich pomegranate extract and EA improved cognitive impairments and brain dysfunction by up-regulating CREB/BDNF signaling in rodents, 53,54 which is in line with our results. It seems that CREB signaling may be a common target of both UroA and its precursors.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, BAE significantly ameliorated the ERK/CREB/BDNF signaling suppressed by AA in the hippocampus ( Figure 7 ), suggesting that the BDNF pathway may be a potential molecular target for dietary anthocyanin. Consistent with our findings, supplementation of pomegranate-derived anthocyanins can improve the CREB/BDNF pathways and alleviate cognitive impairments in an opioid-dependent rat model [ 36 ]. As previously reported, GSH deficiency and IL-1 β administration can impair the expressions of BDNF in the hippocampus of rats [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, DeltaFosB has been linked to drug-related behaviors through affecting the overexpression of dopamine receptor-1 in the NAc inducing reward sensitization (Nestler, 2008;Russo et al, 2009) leading to organic and behavioral changes (Ruffle, 2014). Recent evidence in morphine-administered mice has pointed out the positive effects of anthocyanins present in pomegranate by reducing MORs and cyclic AMP (Ridzwan et al, 2020). This molecular pathway is crucial in opioid dependence and withdrawal (Browne et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…craving of patients under MAT towards their trajectory to successful rehabilitation. Concerning psychosocial parameters, it appears to be beneficial against impaired cognitive function inopioid-dependent in vitro and in vivo models (Cambay et al, 2011; Hajipour et al, 2014;Ridzwan et al, 2020). Moreover, pomegranate seems to be effective on depression and anxiety of OUDs patients (Abu Taweel and Al Mutary, 2021) as well as on the improvement of impaired behavioral aspects ameliorating aggressiveness through the inactivation of ROS, whose enhanced levels have been associated with aggressive behavior(Felippe et al., 2021).…”
mentioning
confidence: 99%